THE EFFECT OF MIND MAPPING MODEL OF LEARNING OUTCOMES OF FIFTH GRADE STUDENTS IN GEOMETRIC MATERIAL AT SD NEGERI 99 PALEMBANG - Rahmah, Nabilah; Harini, Bunda (Jurnal Ilmiah Teunuleh, 2022)
This study aims to determine the effect of the application of the Mind Mapping model on the learning outcomes of fifth grade students in geometric material at SD Negeri 99 Palembang. The method used in this research is the Pre-Experimental Design with the type of One group Pretest-Posttest Design. The sample in this study were fifth grade students consisting of 24 male students and 20 female students. The research instrument used in this study is tests and documentation. Based on the results of data analysis, the average pretest score was 39.99 and the average posttest score was 54.69. Based on the hypothesis test, the value of Sig. (2-tailed) = 0,000 which means less than 0,05 with a significant level of 5%. Thus H0 is rejected and Ha is accepted, so it can be concluded that the Mind Mapping learning model has an influence on the learning outcomes of grade 5 students in geometric material at SD Negeri 99 Palembang.